Pengaruh penambahan pati biji durian terhadap kualitas kimia dan organoleptik nugget ayam - Meitta Ageng P; Djalal Rosyidi; Eny Sri Widyastuti (Faculty of Animal Science, Universitas Brawijaya, 2013)
The research aims at evaluating the effect of durian seed starch addition for chemical and organoleptic properties of chicken nuggets. Randomized Block Design was used in this research by using four treatments and five times replication, and continued with Duncan’s Multiple Range Test Method. Durian seed starch used with four different levels (0%, 5%, 10%, and 15%) was added to the dough of chicken nuggets. Chemical quality variables measured were water, fat and protein content, while the variable was measured on the organoleptic were texture, taste and flavor. The result showed that durian seed starch was used with different levels given effects of water content, fat content, texture and flavor. The best result was chicken nuggets made with added of durian seed starch 5%, the average percentage of water, fat, protein, preference of texture, taste and flavor in chicken nugget with the addition of durian seed starch were 70.59; 2.23; 16.90; 3.31; 3.81; and 4.10 respectively. The conclusion of this research was effect addition of durian seed starch on chicken nugget decreased contents of water, fat and protein, value of flavor and taste, but increased the value of texture.Keywords: chicken nuggets, durian seed starch